Stúdium lokálnych anestetik. Cast' 183: micelizácia a termodynamické parametre heptakaíniumchloridu v prostredí roztoku KBr - Andriamainty, F; Cizmárik, J; Malík, I; Horvat, S (Ceska a Slovenska farmacie, 2008)
The critical micellar concentration (CMC) of the local anaesthetic agent heptacainium chloride in the solution of KBr was determined by the spectrophotometric method in the UV region of the spectrum at the temperature range of t = 20-40 degrees C and pH = 4.5-5.0. The dependence of CMC on the temperature T turned out forming the U-shape with the minimum at the temperature of t = 25 degrees C. The parabolic dependence of CMC on the temperature T was drawn by the fitting of the values using the polynomial function and the so-called power law equation. The CMC dependence on the temperature T was fitted by the second degree polynomial function. The obtained parabolic equations were applied to the "phase separation model", so the following thermodynamic parameters could be calculated: standard Gibbs free energy (deltaG), enthalpy (deltaH degrees), and entropy (deltaS degrees). The thermodynamic parameters were further used to determine the so-called entropy-enthalpy compensation of the systems under study. The compensation temperature was in the following range: (301 +/- 1-303 +/- 3)K. Then the temperature dependence of the enthalpy (deltaH degrees) and entropy (-TdeltaS degrees) contributions to the standard Gibbs free energy (deltaG degrees) for all prepared concentrations of the compound were calculated.
Keywords: bromidy; farmaceutická chemie; sloučeniny draslíku; anestetika lokální; roztoky; termodynamika; Piperidines; micely; Potassium Compounds; Solutions; Anesthetics, Local; Micelles; piperidiny; Thermodynamics; Chemistry, Pharmaceutical; Bromides